Clinical care and interdisciplinarity in heart disease (Research, Society and Development, 2022)
Objective: To analyze the relationship between clinical care and interdisciplinarity in heart disease. Method: Theoretical-reflective study aimed at reflecting on the concept of interdisciplinarity articulated to the clinical care of patients with heart disease, which emerged from discussions and debates during the discipline of Concept of clinical care and health management, in the postgraduate course in Clinical Care in Nursing and Health at the State University of Ceará. The reflections were based on readings of scientific articles, books and documents, with the search for articles in the VHL, SciELO, CINAHL and PubMed portal, in March and April 2022. Two categories emerged: Clinical care in the context of heart disease and Interdisciplinarity in the clinical care of patients with heart disease. Results and discussion: The categories brought aspects related to the complexity of the patient with heart disease requiring care beyond a health condition, with a view of protection and promotion of quality of life, as well as the importance of interdisciplinary work based on actions joint decisions and shared decisions among the team. Final Considerations: The practice of clinical care for patients with heart disease involves a range far from the limited performance of a single professional, but within the perspective of interdisciplinarity, aiming at an integral care combined with the complexity that this type of patient needs, with a view differentiated that a trained team that works together, with a focus on the patient, can provide through humanized, integrated care and with a holistic view.